A Serial Micro-Fibrinolysis Test and Its Use in Rats with Liver-Bypass - Wasantapruek, S; von Kaulla, K. N (Thrombosis and Haemostasis, 1966)
A micro-euglobulin lysis test is described for serial testing in individual rats. With the method it was shown that the rat a) responds well with a fibrinolytic reaction to carbachol, b) that a liver-bypass in this animal produces a sustained fibrinolytic reaction which c) after subsiding can be re-established by carbachol and that d) the fibrinolytic phase in rats with liver-bypass lasts longer after preceding splenectomy and adrenalectomy.